English Language Teaching in a Humanitarian Context: A Study of Features and Parameters Affecting Vulnerable Learners in Iraq - Al-Shamali, Farah Mohammad (2024)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Farah Mohammad Al-Shamali entitled, “English Language Teaching in a Humanitarian Context: A Study of Features and Parameters Affecting Vulnerable Learners in Iraq”, submitted in November 2024. Thesis advisor is Dr. Ozgur Parlak. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).